Monsterrat : emerald isle of the Caribbean - Fergus, Howard A. (Macmillan Publishers LondonGB, 1986)
Describes the topography and climate of Montserrat, its history, flora and fauna, government, people, culture and economy. Provides information on accomodation, education, medical services, and cuisine.